Cognitive systems evolution: immigrant last generations and cognitive mapping - Figueiredo, Sandra (2018)
There is little evidence on the correlation between immigration effects and the evolution of the mind and cognition, especially concerning children. Last generations of young immigrants are expected to experience adaptive strategies to respond to the school environment in order to achieve success. Specifically concerning the new language learning in the diversity of the host countries (plus the diversity of the countries of origin and home languages/cultures), it should be analyzed how the human cognitive aptitude (language aptitude and problem solving) is being reorganized in terms of thought, concepts and cultural orientations previously developed in a certain native culture. The native culture (aspects of the nationality and of the home language) is mentally associated to concepts and generates the self-regulation which implies consciousness in a home culture as a reference. How does it works for new immigrants that were separated (including cases of forced immigration) from their unique cognitive reference? Different cognitive achievements and language deficits would be constrained in their natural development and differences in academic achievement are expected. This lead to implications for the biological hypothesis of critical period concerning the new waves of immigration and ethnic differentiation in current generations. Age would be considered along with other unexpected variables such as nationality. The present study examines populations’ differences – ethnic and age – on specific language and cognitive tasks considering immigrant students in Portuguese schools (M=13 years old; SD= 2,7) with origin in different world areas: Western Europe, Eastern Europe, African countries, Latin America, Asia (Indian Asia) and China and with different home languages and cultures. Data showed a variability of groups’ achievements in cognates, text recall, lexical recall and dichotic listening tasks. Disparities among the minorities will be discussed considering educational and ethological implications. Population evolutionary characteristics might be concluded from those disparities.